Molecular Epidemiology of HIV-1 Infection among Men who Have Sex with Men in Taiwan in 2012 - Huang, Szu-Wei; Wang, Sheng-Fan; Cowó, Ángel E.; Chen, Marcelo; Lin, Yu-Ting; Hung, Chun-Po; Chen, Yi-Hsien; Yang, Jyh-Yuan; Tang, Hung-Jen; Chen, Yi-Ming Arthur (PLOS ONE, 2015)
The number of men who have sex with men (MSM) infected with HIV-1 in Taiwan has increased rapidly in the past few years. The goal of this study was to conduct a molecular epidemiological study of HIV-1 infection among MSM in Taiwan to identify risk factors for intervention. Voluntary counseling program and anonymous testing were provided to patrons at 1 gay bar, 7 night clubs and 3 gay saunas in Taipei and New Taipei Cities in 2012. HIV-1 subtypes were determined using gag subtype-specific PCR and phylogenetic analysis by env sequences. Recent HIV-1 infection was determined using LAg-Avidity EIA. In-depth interviews and questionnaires were used to identify risk factors. The prevalence and incidence of HIV-1 among MSM in Taiwan were 4.38% (53/1,208) and 3.29 per 100 person-years, respectively. Of 49 cases genotyped, 48 (97.9%) were infected with subtype B and 1 with CRF01_AE (2%). Phylogenetic analysis of 46 HIV-1 strains showed that 25 (54.4%) subtype B strains formed 9 clusters with each other or with other local strains. The CRF01_AE case clustered with a reference strain from a Thai blood donor with bootstrap value of 99. Multivariate logistic regression analysis showed that risk factors associated with HIV-1 infection included use of oil-based solution as lubricant (vs. saliva or water-based lubricants, OR= 4.23; p <0.001); exclusively receptive role (vs. insertive role, OR= 9.69; p <0.001); versatile role (vs. insertive role, OR= 6.45; p= 0.003); oral sex (vs. insertive role, OR= 11.93; p= 0.044); times of sexual contact per week (2-3 vs. zero per week, OR= 3.41; p= 0.021); illegal drug use (OR= 4.12; p <0.001); and history of sexually transmitted diseases (OR= 3.65; p= 0.002). In conclusion, there was no new HIV-1 subtype or circulating recombinant form responsible for the increase of HIV-1 among MSM in Taiwan in 2012. Misuse of oil-based solution as lubricant is a new risk factor identified among MSM in Taiwan. The Taiwan’s Centers for Disease Control has created a video (www.youtube.com/watch?v=BinExvvOTMM&feature=iv&src_vid=BW81-PfmY3E&annotation_id=annotation_2436493705) to correct such misconception in its AIDS prevention campaign.